The Influence of Public Misconceptions About Indie Music on the Popularity of the Folk Genre in the General Society - Ibnu Amar Muchsin; Reza Pahlevi Sugianto (Universitas Pendidikan Indonesia, 2023)
With the popularity of music and indie bands today, it turns out there are still a lot of people who don't know what an indie is and who can't tell it from the folk genre. The study therefore aims to see how much community misconceptions about indie music can affect the popularity of the folk genre. The study was done by the distribution of Google form questions to respondents who are in the general population of all classes and of all ages. The study was tested using Validation Test, Reliability Test, Normality Test as well as Simple Linear Regression Tests. From that series of tests researchers came to the conclusion that indeed, public misconceptions about indie music had an effect on the popularity of the folk genre in the community.